Risk factors for failure of class V restorations of carious cervical lesions in general dental practices. (October 2018) - Wierichs, R.J.; Kramer, E.J.; Meyer-Lueckel, H.
Abstract: Objectives: The aim of this retrospective, non-interventional, multi-center, practice-based study was to analyze factors influencing the survival of restorative treatments of one- and two-surface active cervical (root) caries lesions (CCLs). Methods: Records from patients who visited five private practices regularly were searched for the presence of active one- and two-surface CCLs. Data from 1167 patients with 2070 CCLs being detected at least 6 months before the last recall visit were recorded. Kaplan-Meier-analyses were used to analyze time-to-failure. Cox proportional hazards models were used to evaluate the association between clinical factors and time until failure. Results: Within 120 months [mean (SD) follow-up period:50 (40) months] 219 failures could be observed. Median survival time was 120 months. The AFR was 1.82% for one-surface restorations (CCL1 ) and 3.25% for two-surface restorations (CCL2 ). In multivariate Cox regression two-surface cervical restorations showed 1.75 times higher failure rates than one-surface cervical restoration. Furthermore, CCL being checked up more than twice a year showed significantly higher failure rates than restorations being checked up less than twice a year (p < 0.001). Conclusion: Low failure rates could be found for restorative treatment strategies of one- as well as for two-surface CCLs. Clinical significance: Restorative treatment of CCLs is a viable way to manage one-surface CCLs. However, the proximal extension of the CCL significantly shortens the longevity of the restoration. The study was registered in the German Clinical Trials Register (DRKS-ID: DRKS00012510).